ANALISIS PERTUMBUHAN LABA MENGGUNAKAN PENDEKATAN CAMEL PADA BANK PERKREDITAN RAKYAT DI TANGERANG PERIODE 2014-2016 - Erdawati, Lena; Bachtiar, Mariana (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this research was to determine the influence of CAMEL financial ratio simultaneously and profit growth in partial response to the rural banking company in Tangerang. This Research data used are secondary data are financial statement of the 10 rural Banks District of Tangerang that its financial statements which always makes a profit. This research examined the data published in 2012 until 2016. Indicators of this study is CAMEL indicators of which are: 1) CAR which is the indicator of capital, 2) ROA which is the indicator of asset, 3) NPM which is an indicator of management,, 4) BOPO is an indicator of earning 5) LDR is an indicator of liquidity. Method in collecting data in this research is documentary and library method. The technique of data analysis using data panel regression model, and hypothesis test with EViews program. The result of this research showed that CAR and LDR variables can predict the the profit growth to the rural banking company in Tangerang at 2010-2014. NPM and BOPO variables have significant affect to the profit growth variable while CAR, ROA and LDR variables have no significantly affect the profit growth variable.Keyword: profit growth, CAR, ROA, NPM, BOPO, LDR, profit growth